Characteristics Of Patients Treated In The Emergency Department Of Cicendo Eye Hospital Bandung - Dian Purwitasari; Elfa Ali Idrus; Bagus Ramdan; Astari Nola Margaretha; Muhamad Adli Boesoirie; Patriotika Muslima (Jurnal EduHealth, 2024)
The Eye Hospital Emergency Department in Cicendo, Indonesia, is experiencing an increase in patients seeking treatment due to eye trauma cases, a prevalent issue in Western countries and Asia, including Indonesia. This study aims to determine the characteristics of patients seeking treatment in the emergency room from June-July 2024. The analytic observational method with a cross-sectional approach was used. The results showed that the largest age group of patients was adult males, with an average age of 43 years. The most common complaint was eye pain, with 40% of patients reporting it. The most common eye condition was foreign bodies in the cornea, followed by mechanical trauma, with 12% of patients experiencing corneal abrasion and lacerated eyelid, and 6% of patients experiencing corneal abrasion and lacerated eyelid. Most patients had a history of previous eye disease, which was the same as the diagnosis of a foreign body in the cornea, specifically the eye affected by grams. This study highlights the need for improved emergency care services in the eye hospital.